Transferring Educational Theories and Knowledge Using a Co-Teaching Mentor Model: A Discipline-Appropriate Approach - Turkich, K.; Greive, Shane; Cozens, Paul (University of Wollongong, 2014)
This paper presents a co-teaching mentor model, which improved the teaching of academics and enhanced student satisfaction and retention. Two research-focused lecturers responsible for first-year units were partnered with a co-teaching mentor to offer guidance on how the content (urban and regional planning) could be delivered more effectively with an emphasis on student engagement and motivation. These two case studies are discussed and the findings demonstrate the effective transfer of teaching awareness and skills through this process.Five key educational theories underpin the substantive changes made to the way that classes were delivered. The applied relevance and transfer of these ideas can be demonstrated in the reflections from the participating staff through a pedagogical analysis of the before and after changes in their teaching practices, and in the improved student evaluation and retention results.